INFORMAL ECONOMY, ISLAMIC FINANCE DEVELOPMENT, AND SUSTAINABLE DEVELOPMENT IN MUSLIM-MAJORITY COUNTRIES - Muhammed, Ismail Aremu; Khalid, Ahmed Masood; Premaratne, Gamini (Journal of Islamic Monetary Economics and Finance, 2024)
The paper focuses on the impact of informal economy and Islamic finance development on sustainable development using a panel dataset of 15 Muslim-majority countries from 2016 to 2022. The results based on the feasible GLS and panel quantile regression methods reveal that Islamic finance development has a positive impact on sustainable development. Meanwhile, the informal economy has a negative impact on sustainable development. Assessing the components of Islamic finance development, we further note that only quantitative development/financial performance and knowledge indicators are effective in achieving sustainable development. Besides these key results, GDP per capita, trade openness, and foreign direct investment emerge to be positive factors while the natural resource rents a negative factor in sustainable development. We reason that low productivity and precarious working conditions associated with informal economy may have hindered economic, social, and environmental wellbeing. The positive contribution of the Islamic finance development especially those related to Islamic financial performance and knowledge sharing to sustainable development hints the importance of further development of the Islamic financial sector in these countries.